1996
DOI: 10.1074/jbc.271.2.1029
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Enhances Pancreatic Islet Arachidonic Acid 12-Lipoxygenase Product Generation by Increasing Substrate Availability through a Nitric Oxide-dependent Mechanism

Abstract: Interleukin-1 (IL-1) impairs insulin secretion from pancreatic islets and may contribute to the pathogenesis of insulin-dependent diabetes mellitus. IL-1 increases islet expression of nitric oxide (NO) synthase, and the resultant overproduction of NO participates in inhibition of insulin secretion because NO synthase inhibitors, e.g. N G -monomethyl-arginine (NMMA), prevent this inhibition. While exploring effects of IL-1 on islet arachidonic acid metabolism, we found that IL-1 increases islet production of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 89 publications
(127 reference statements)
5
35
0
Order By: Relevance
“…We have recently reported that IL-1 also induces accumulation of nonesterified arachidonic acid in islets by an NO-dependent mechanism (6). Our findings suggested that this reflected suppression of re-esterification of arachidonic acid released during phospholipid turnover, but others have found that NO stimulates arachidonic acid release from macrophagelike cells by a mechanism involving accelerated glycolytic flux (13).…”
mentioning
confidence: 37%
See 1 more Smart Citation
“…We have recently reported that IL-1 also induces accumulation of nonesterified arachidonic acid in islets by an NO-dependent mechanism (6). Our findings suggested that this reflected suppression of re-esterification of arachidonic acid released during phospholipid turnover, but others have found that NO stimulates arachidonic acid release from macrophagelike cells by a mechanism involving accelerated glycolytic flux (13).…”
mentioning
confidence: 37%
“…induces islet expression of the inducible isoform of nitric oxide synthase and overproduction of nitric oxide (NO) (1)(2)(3)(4)(5)(6). This is associated with inhibition of glucose-induced insulin secretion (7)(8)(9)(10) and impaired islet oxidation of glucose (8 -12), and both of these effects are prevented by the inducible nitric oxide synthase inhibitor N G -monomethylarginine (NMMA) (1, 2, 4), indicating that they occur through NO-dependent mechanisms.…”
mentioning
confidence: 99%
“…This amount of each cytokine in combination has been shown to consistently impair glucose-induced insulin production in uninfected islets, as well as in those infected with the Ad-LacZ control virus. 7,8,17,18,[33][34][35][36][37][38][39] In dynamic glucose perifusion studies, we observed that TNFa addition for 18-24 h was sufficient to significantly reduce islet sensitivity to glucose (assessed by insulin production). The combination of TNFa and IL-1b almost completely suppressed insulin production ( Figure 1b and Table 1).…”
Section: Ad-tnfr-ig Gene Transfer To Islets Results In High Tnfr-ig Pmentioning
confidence: 83%
“…12-Lipoxygenase is expressed in rodent and human islets [11,[15][16][17][18] and is upregulated under conditions of metabolic and cytokine stress. Direct addition of 12-S-HETE can impair beta cell function or can lead to loss of human beta cell viability [13,15,16,[19][20][21][22]. Recent evidence indicates that increased expression of 12-lipoxygenase in islets is a common feature of both rodent and human models of type 1 and type 2 diabetes [11,13,15,17,22].…”
Section: Introductionmentioning
confidence: 99%